Green Hotel Concept and Practices in Indonesia - Yuniati, Nining (E-Journal of Tourism; Volume 8 Number 2 (September 2021), 2021)
The term of green hotel is still less popular in the community, tourists and even tourism practitioners, as well as many people who do not understand the definition and practice. In Indonesia, green hotels remain an important concern for the government and the private sector regarding the contribution to environmental preservation and reducing the impact of global warming. The application of the green hotel concept still raises pros and cons due to a number of burdensome requirements for business actors. They mostly assume green hotel is a burden and will reduce the comfort of hotel guests. Eventhough in terms of tourists side many of them need green hotel, but in fact not all travelers understand about the green hotel, especially in Indonesia. This paper examines a number of green hotel empirical concepts and facts that have been conducted in various countries and then compares with Indonesia. The case in Yogyakarta is an example on how tourists have not fully understood the concept of green hotels